New Model of School Inspection focused on evaluation and improvement - Estefanía Lera, José Luis (Avances en Supervisión Educativa, 2021)
Need to evolve from a bureaucratic, norm-focused model to one that relies on schools' experience. This entails a change of strategy and method of the School Inspection.Supervision should be more contextualized and collaborate more with the educational centres. Control and advice must be more preventive, group-focused and formative. School Inspection should focus on the schools' projects' monitoring and results. And the educational centres should carry out these projects in the use of their autonomy. The evaluation of the school’s directors and docents must prevail over other actions. This guarantees the quality of teaching. Moreover, it establishes the evaluation for improvement, self-evaluation and results achievements.
Keywords: school inspection model; functions of the school; inspection; autonomy of educational centres; evaluation; self-evaluation; improvement